Semideciduous seasonal forest opiliofauna (Arachnida, Opiliones), State of Paraná, Brazil (Acta Scientiarum. Biological Sciences, 2021)
Harvestmen are arachnids that play an important role in organic matter breakdown. However, there are many ecosystems in Brazil, including Conservation Units, which lack information about these organisms or are sub-sampled. Even in areas of Atlantic forest, a biome that hosts the greatest diversity and endemic rates of these arthropods in the world. In this perspective, the purpose of this study was to survey the harvestmen fauna in areas of Semideciduous Seasonal Forest in the Ilha Grande National Park, Paraná, southern Brazil, from February to November 2019, totaling 15 days and 60 hours, on six islands in the Paraná River. A total of 170 specimens was collected, distributed in five genera, comprising two species and three morphotypes. The low species richness may reflect the isolation of populations imposed by the island effect, however the study expanded the geographic distribution of Parapachyloides uncinatus and Discocyrtus invalidus, for which until then there was no record of occurrence in the Paraná State.